2009
DOI: 10.1021/ma9012829
|View full text |Cite
|
Sign up to set email alerts
|

Nitroxide-Mediated Radical Polymerization of Styrene in Aqueous Microemulsion: Initiator Efficiency, Compartmentalization, and Nitroxide Phase Transfer

Abstract: Nitroxide-mediated radical polymerizations (NMP) of styrene at 100 °C using the cationic emulsifier tetradecyltrimethylammonium bromide (TTAB) have been carried out employing 2,2′-azoisobutyronitrile (AIBN) and two nitroxides of different water solubilities. The polymerization rate was lower and the molecular weight distribution more narrow in microemulsion than bulk at low conversion. The results can be rationalized based on the lower initiator efficiency in microemulsion than bulk, presumably caused by the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 57 publications
5
45
1
Order By: Relevance
“…Despite the fact that the present system is a miniemulsion (kinetically stable but thermodynamically unstable), it is interesting to compare the particle size data with previous microemulsion (thermodynamically stable system) NMP data, since the initial droplet/particle sizes are similar (approximately 25 nm). The d n versus conversion data in the present study are in sharp contrast to the styrene microemulsion NMP data previously reported by Zetterlund et al [23] (SG1/AIBN), which exhibited very small particle sizes at low conversion (d n ¼ 23 nm; translucent appearance), but the particle size gradually increased with conversion to reach 55 nm (opaque appearance) at 92% conversion. The conversion-time plots in the present work, as well as in the above-mentioned microemulsion NMP, are close to linear.…”
Section: Nitroxide-mediated Radical Polymerizationcontrasting
confidence: 98%
See 3 more Smart Citations
“…Despite the fact that the present system is a miniemulsion (kinetically stable but thermodynamically unstable), it is interesting to compare the particle size data with previous microemulsion (thermodynamically stable system) NMP data, since the initial droplet/particle sizes are similar (approximately 25 nm). The d n versus conversion data in the present study are in sharp contrast to the styrene microemulsion NMP data previously reported by Zetterlund et al [23] (SG1/AIBN), which exhibited very small particle sizes at low conversion (d n ¼ 23 nm; translucent appearance), but the particle size gradually increased with conversion to reach 55 nm (opaque appearance) at 92% conversion. The conversion-time plots in the present work, as well as in the above-mentioned microemulsion NMP, are close to linear.…”
Section: Nitroxide-mediated Radical Polymerizationcontrasting
confidence: 98%
“…This value of f is somewhat lower than what is normally obtained in bulk/solution systems. [58] It has previously been reported that f is lower in microemulsion than in bulk for SG1-mediated polymerization of styrene at 100 8C, [23] attributed to increased levels of geminate termination of initiator radicals generated in pairs in small particles (the confined space effect), [51][52][53][54][55] and it would appear that this rationale also applies to the present data considering the very small particle size. The particle size decreased somewhat with increasing conversion (d n ¼ 25 and 13 nm at 0 and 92% conversion, respectively; Figure 2), which would appear to indicate secondary nucleation.…”
Section: Nitroxide-mediated Radical Polymerizationsupporting
confidence: 69%
See 2 more Smart Citations
“…The potential of microemulsion polymerisation has yet to be fully realised for solvophobic block copolymer syntheses, although the few published examples suggests that highly pure products can be obtained, 97,118 which may be a direct result of confinement effects, where termination and radical side reactions are suppressed. 154,155 Methods in which the monomer is initially soluble and the growing polymer precipitates can further simplify the polymerisation process i.e. dispersion and precipitation polymerisation.…”
Section: Nmpmentioning
confidence: 99%